Fee-Based Services in ADA University Library - Mammadov, Elchin (ADA University, 2019)
The mission of the presented Business Consultancy Project is to provide theoretical and practical deliveries about possibility of the additional profit from generated services in ADA University Library. These kind of academic library services are implemented successfully in many developed countries, but they still are very new concepts in local milieu. Even today we passed almost 1/4 of XXI century, but many Academic Libraries, Public and School in Azerbaijan lack on the areas like information acquisition and exchange, budget planning and management, access to latest published resources, the quality of the information, information services and many related issues. Besides technological issues there is a lack of qualified librarians who can lead sustainable libraries. From another point of view the priority customer segment (faculty and students) of academic libraries are experiencing language and information literacy shortages. According to surveys conducted in the University libraries in Baku, the answer to the question – “Why do you keep card catalogs and don’t you have demand to eliminate them?” – was – “the professor can’t use the library electronic catalogs and discovery tools, also they have language barriers”. In general, there is continuing process of segregation of the Universities by instruction languages which impacts formation of the Library collections very much. In the last decade, ADA University Library has been becoming one of the leading academic information services entity in Azerbaijan. Adoption and integration of new concepts may increase efficiency and create new market opportunities in local environment. According to investigation the expenses and investment of the ADA University rising for sustaining library and information services and operations. Finding additional revenue streams, donors and partners becoming necessity. Rationale. The project starts with rationale introducing libraries, technology and profit generation issues in brief, continuing with statement of the problem and answers to the questions found in the study. The main purpose of the study is to make some positive changes in academic library structure, to develop new profit generated directions in ADA University Library. Analysis of the academic literature and global experiences creates many new ideas, formulates some objectives and compares various approaches of authors. The research and analysis are dedicated to mechanism of organization and management of the fee-based library services. How new profit generated services will impact customer`s experience of using library resources is studied throughout the research. How stakeholders will be allocated and will be part of this process, what will be the benefits of fee-based library services in Azerbaijan are other issues covered by this paper. In the Background part the study describes about today's libraries’ expenditure, needs, experiencing budget constraints. Also emerging of fee-based services, history and development, challenges of organization are given in this part. Successful practical results from global library and information institutions are presented. Following, local environment, the current circumstances and practices, opportunities and obstacles for fee generating services in the public, academic and school libraries of Azerbaijan are analyzed. Based on that theoretical and practical implications ADA University Library case was over viewed. General information, types of services, working hours, cost centers, development perspectives were provided. Conducted current SWOT and TOWS analyses to know the strength and weaknesses, how overcome the threats and benefit from opportunities. For the Methodology part 1. Visited to various libraries and interviewed library directors and ordinary librarians, how they see the perspectives of fee-based library services, are they have any vision on these kind of activity. 2. Designed and conducted applications for ADA University Library user, as well as surveys and live interviews. The goal was to understand the customers` research and information needs, in order to acquire demanded collections and provide required services, to make minimum “NO” answers. Survey questions consist of 17 questions intended fro three type of stakeholders: Library and Information Centers, External Users (individual) and (corporate ) of ADA University Library. Modeled SWOT and Business Canvas for fee-based library services for ADA University Library. In the part Outcome and Analysis results of collected data were provided. Referring analysis on primary data there are drawing not positive picture, but still not late and there is an opportunity. The libraries in Azerbaijan doing a tentative actions on fee generating services. Among 13 various types of libraries researched only three entities currently organizing some fee-based services: Azerbaijan National Library, ADA University, Oxbridge Academy Library. Another outcomes related with ADA University Library external visitors both individual and corporate. There was an interesting view. The most information resources acquired by ADA University Library have uniqueness comparing with other libraries 45.6% approached for textbooks and related materials. Also experiencing increase in demand in professional development cases 43% (121 out of 281) of surveyed and interviewed applicants. Another distinctive feature of ADA University library, providing reliable resources where about respondents from individual and corporates 70% are favor of reliable resources. As well as there is a huge interest to electronic resources and online databases acquired by ADA, where applicants responded for e-books, e-resources 17.1% and Online e-databases 5.7%. To the question about fee-based library services the both individual and corporate applicants (about 80%) responded quite positive, but with different access level options that related with copyright, technical and location issues. In the practical realization part Project Implementation Circumstances, the legal and technical levels of resources’ consumption in ADA University Library was depicted. Identified the roles of staff members base on Responsibility Matrix. Investigate expenses of ADA University Library in order to set prices and periods foe fee-based services. As well as shortly represented economic feasibility and limitations. Conclusion and recommendations part is last part of the project and gives summary of study, stressing the shortages and benefits, the key areas where need to be more attentive. The end notes are the recommendations which can be useful for future development of fee-based library services in ADA University Library.
Keywords: Business; Library finance.; Fee-based library services.; Library management.; Azerbaijan -- Libraries -- Financial aspects.; Information services -- Finance.